Reference values for spirometry in elderly individuals - Belo, Joana (2018)
Background: Spirometry is the single most important test for the evaluation of respiratory function. The results are interpreted by comparing measured data with predicted values previously obtained from a reference population. Reference equations for spirometry have been discussed previously. The aim of this study was to compare reference values based on National Health and Nutrition Assessment Survey (NHANES III), European Community of Steel and Coal (ECSC), and Global Lung Initiative (GLI) equations in an elderly sample population. Methods: Subjects from the Geriatric Study on Health Effects of Air Quality in elder care centres who met the inclusion criteria were enrolled. Spirometry was performed according to international guidelines. The forced vital capacity, forced expiratory volume in 1 s, and FEV1/FVC ratio were reported as percentages of the predicted value, and the lower limit of normality was calculated. Results: Out of 260 elderly patients, 69.6% were women; the mean age was 83.0 ± 6.46 years with an age range of 65-95 years. The lowest %FVC and %FEV1 values were obtained using the GLI reference equations. However, when NHANES III equations were used, the FEV1/FVC ratio was higher than ratios obtained from GLI and ECSC equations. The prevalence of airway obstruction was highest using ECSC equations, while GLI equations demonstrated more restrictive defects. Conclusions: The present study showed meaningful differences in the reference values, and consequently, in the results obtained using NHANES III, ECSC, and GLI reference equations. The spirometry interpretation was also influenced by the reference equations used.